EFL Teachers’ Perspective on The Implementation of AI In ELT Setting - Sahdrina, Sahdrina; Erlindawaty, Erlindawaty; Adinda, Adinda (Lembaga Riset Mutiara Akbar, 2024)
This study investigates the perspective of English teachers regarding the utilization of Artificial Intelligence (AI) as a tool in the English Language Teaching (ELT) setting. The current research employed a convenience sampling technique to choose a sample of 346 students from 12th grade classes at SMAN 16 Medan. Data was gathered by the processing of questionnaires and conducting interviews with the teachers. A subsequent analysis of the data was carried out using SPSS version 29.0. The findings suggest that students support the incorporation of Artificial Intelligence in English Language Teaching (ELT) as a technological tool. Given the limited availability of the incorporation of Artificial Intelligence does not affect individuals’ positive view points about the importance of the utilization of Artificial Intelligence as an educational tool. The positive viewpoint of the teachers about implementing Artificial Intelligence into the development of educational tools in ELT Setting. The concern expressed by the teachers on the application of Artificial Intelligence highlight the multitude of the utilization of these tools for learning greatly enhances the efficacy of the learning and teaching process